2016
DOI: 10.4184/asj.2016.10.6.1091
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenic Protein Is a Viable Adjunct for Fusion in Minimally Invasive Transforaminal Lumbar Interbody Fusion

Abstract: Study DesignComparison of prospectively collected data of patients undergoing minimally invasive surgery transforaminal lumbar interbody fusion (MIS-TLIF) with and without recombinant human bone morphogenic protein 2 (BMP).PurposeTo compare the clinical, radiological outcome and complications of patients undergoing MIS-TLIF with and without BMP.Overview of LiteratureBMP is an effective fusion enhancer with potential complications. Direct comparison of MIS-TLIF with and without BMP is limited to retrospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In a prospective study of 252 patients, Siddiqui et al obtained fusion rates of 88.4% and 98.5% at six-month and two-year follow up, respectively. Compared to patients treated with other materials (autograft and/or DBM), the rhBMP-2 group achieved a significantly greater rate of fusion at the six-month interval (88.4% vs. 76.8%, P=0.016), though there was no difference between groups two years (41). In this study, patients underwent fusion with an interbody cage packed with autograft and rhBMP-2, and the remaining disk space was filled with autograft alone (41).…”
Section: Bone Morphogenetic Protein-2 (Bmp-2)mentioning
confidence: 76%
“…In a prospective study of 252 patients, Siddiqui et al obtained fusion rates of 88.4% and 98.5% at six-month and two-year follow up, respectively. Compared to patients treated with other materials (autograft and/or DBM), the rhBMP-2 group achieved a significantly greater rate of fusion at the six-month interval (88.4% vs. 76.8%, P=0.016), though there was no difference between groups two years (41). In this study, patients underwent fusion with an interbody cage packed with autograft and rhBMP-2, and the remaining disk space was filled with autograft alone (41).…”
Section: Bone Morphogenetic Protein-2 (Bmp-2)mentioning
confidence: 76%
“…As a result, BMPs seem to acquire osteoinductive characteristics, and therefore, they have been studied for their bone healing and growth potential [ 32 ]. To circumvent post-operative morbidity and complications after harvesting ICBG, the recombinant human BMP-2 (rhBMP-2) is employed as a potent bone graft enhancer [ 165 ]. Clinically, rhBMP-2 has been proven not only to improve bone fusion but also improve recovery in back pain [ 166 ].…”
Section: Currently Employed Surgical Materials For Bone Grafting Amentioning
confidence: 99%
“…However, two large-scale retrospective studies with a combined cohort of over 600,000 patients concluded that there is no evidence of increased malignancy with the use of rhBMP-2 [ 110 , 111 ]. From the 8 studies that met our inclusion criteria utilizing rhBMP-2 in MIS-TLIF, Nandyala et al documented a case of rhBMP-2 related neuroforaminal bone growth and cage migration/osteolysis and Siddiqui et al reported two cases of bone overgrowth with radiculopathy, a case of osteolysis, and two cases of radiculitis [ 49 , 70 ].…”
Section: Bone Graft Materialsmentioning
confidence: 99%
“…While the site of rhBMP-2 insertion can vary based on surgeon preference and the pathologies, the relative dose of rhBMP-2 also differed. Of all the MIS-TLIF studies we included, Tsahtsarlis and Wood, Siddiqui et al, and Nandyala et al reported using 1.4 mg, 4.2 mg, and either 4.2 mg or 12 mg, respectively [ 49 , 70 , 71 ]. Notably, the majority of these studies used CT scans as the method of evaluation for fusion during their postoperative follow-ups ( Table 3 ).…”
Section: Bone Graft Materialsmentioning
confidence: 99%